PENDIDIKAN KARAKTER DALAM NOVEL RANAH 3 WARNA KARYA AHMAD FUADI - Kadariah, Putri; Faizah, Hasnah; ', Syafrial (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: This study described an educational character in the novel Ranah 3 Warna written by Ahmad Fuadi. The aim of this study was to determine the educational character which contained in the novel Ranah 3 Warna written by Ahmad Fuadi. This study was a descriptive qualitative research. The data source of this study was the novel Ranah 3 Warna written by Ahmad Fuadi which consisted of 51 sections with a thickness of 469 pages. Based on the research that conducted by the writer, there are 164 data in the novel that contains educational character. Educational characters which found in the novel Ranah 3 Warna written by Ahmad Fuadi are: (1) Religious, (2) honest, (3) tolerance, (4) discipline, (5) hard work, (6) creative, (7) independently, (8) democratic, (9) curiosity, (10 ) spirit of nationality, (11) love of the country, (12) cherishes the achievements, (13) friendly/communicative, (14) love peace, (15) likes to read, (16) care for the environment, (17) social care, and (18) responsibility.Key Word: Educational Character